Early Proterozoic orogenic activity adjacent to the Hopedale block of southern Nain Province - Ermanovics, Ingo; Ryan, Bruce (Geoscience Canada, 1990)
Summary The Hopedale block of the southern ArcheanNain Province forms a wedge between the Early Proterozoic Makkovik and Churchill provinces. Lower Proterozoic supracrustal rocks, deposited on the Hopedale block following intrusion of tholeiitic dykes ca. 2200Ma, were reworked at amphibolite faciès, and thrust westward against undeformed portions of the block during orogeny in theMakkovik Province. The Makkovik/Hopedaleblock structural boundary Is marked by alate, greenschist-facies dextral shear. By contrast, the boundary between the Hope-dale block and the Churchill Province to the west is a fault zone that separates lower Proterozoic supracrustal rocks, deposited on a protocontinent of Churchill Provincerocks, from fundamentally different rocks ofthe Nain Province. The intensity of Early Proterozoic deformation and metamorphismrises progressively from sub-greenschist fades In the Hopedale block to granulite fades in the interior of the Churchill Province.